Effect of water-to-quick setting cement ratio and aggregate size on mechanical properties and dimensional accuracy of binder jetting 3D-printed bodies - Mursaleen Shahid; Vincenzo M. Sglavo (Open Ceramics)
Quick setting cement-based materials were produced in the present work using the binder jetting 3D printing (BJ3DP) technique with the aim at investigating how processing parameters like water-to-cement ratio and aggregate size affect the final properties of the products. Commercially available quick-setting cement and siliceous sand were utilized. Dimensional accuracy, compressive and flexural strength were measured for variable processing conditions and their individual effect was analysed. The results showed that the properties of printed parts are significantly influenced by the considered processing variables and, in particular, a larger water-to-cement ratio has a beneficial effect on the mechanical performances, the improvement being higher when coarser siliceous sand is used. It was also shown that the employment of finer sand results in more limited dimensional accuracy.